Changes in Histaminergic System in Neuropsychiatric Disorders and the Potential Treatment Consequences - Shan, Ling; Swaab, Dick F. (Current Neuropharmacology, 2022)
In contrast to that of other monoamine neurotransmitters, the association of the histaminergic system with neuropsychiatric disorders is not well documented. In the last two decades, several clinical studies involved in the development of drugs targeting the histaminergic system have been reported. These include the H3R-antagonist/inverse agonist, pitolisant, used for the treatment of excessive sleepiness in narcolepsy, and the H1R antagonist, doxepin, used to alleviate symptoms of insomnia. The current review summarizes reports from animal models, including genetic and neuroimaging studies, as well as human brain samples and cerebrospinal fluid measurements from clinical trials, on the possible role of the histaminergic system in neuropsychiatric disorders. These studies will potentially pave the way for novel histamine-related therapeutic strategies.
Keywords: histamine receptors